Aktivitas Anti Luka Bakar dari Gel Minyak Kemiri (Aleurites moluccana L.) terhadap Tikus Putih (Rattus novergicus) - Leny, Leny; Ginting, Evi Ekayanti; Laia, Warnus; Hafiz, Ihsanul; Tarigan, Jacub (Jurnal Farmasi Udayana, 2021)
Candlenut oil is often used as a traditional medicine that is used topically, generally used to treat hair and treat burns. The purpose of this study was to test the anti-burn activity of candlenut oil which has been formulated in the form of a gel. The method used was a laboratory experimental where candlenut oil was formulated in gel containing various concentrations of active substances 15, 20 and 25%, then tested for burn wound healing activity in mice induced by hot plates. Observation of wound healing time was carried out for 21 days. The results showed that 25% candlenut oil gel were similar to the positive control Burnazin ® in healing burn wound. All of the candlenut oil gel formulas were completely fulfilled the requirement for gel preparation and have activity to heal burn wound. Keywords: Aleurites moluccana , burn wound healing activity, gel